Pemenuhan Hak Atas Pendidikan Dasar bagi Komunitas Adat Terpencil di Provinsi Nusa Tenggara Timur - Firdaus, Firdaus (Jurnal HAM, 2013)
The purpose of the study was intended to determine the policy of the local government in the fulfillment of the right to basic education , and any obstacles encountered in the context of primary education in remote indigenous areas . The purpose of the study was intended to determine the policy of the local government in the fulfillment of the right to basic education , and any obstacles encountered in the context of primary education in remote indigenous areas . The data used in this study is a secondary data collected by literature search ( library research ) and primary data (field research ) that the data collected from each subject , in this case the informant Department of Education , Principals & teachers ( formal ) , organizers of non education informal ( outside of school ) , Community leader / religious , NGO , parents , and Children of primary school age ( which is still in school and dropping out of school ) . While the primary data collection tool was the interview will be made to suit the needs of the target group of the study. The study sample was taken from the whole group / unit Belu District Education Office in East Nusa Tenggara Province . Local Government Policy in the fulfillment of basic education rights to people in remote indigenous communities have been working to improve the quality and quantity of basic education primary school . At the local government level , there are efforts in basic education budget allocated in the budget although it has not reached 20 % as stated in the Constitution of the Republic of Indonesia Year 1945 . Constraints faced in the provision of basic education in the region is limited infrastructure and educators both in quantity and quality . Agencies active in implementing basic education programs in addition to the education office is the Regional Office of Religious and Social Service programs through family expectations (PKH) .